2009
DOI: 10.1186/gb-2009-10-10-r110
|View full text |Cite
|
Sign up to set email alerts
|

NeMeSys: a biological resource for narrowing the gap between sequence and function in the human pathogen Neisseria meningitidis

Abstract: The genome of a clinical isolate of Neisseria meningitidis is described. This and other reannotated Neisseria genomes are compiled in a database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
137
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(141 citation statements)
references
References 56 publications
4
137
0
Order By: Relevance
“…Using this method, a total of 375 distinct proteins were quantified from both the 32°C and 37°C conditions (see Table S1 in the supplemental material). All quantified proteins were classified according to their known or predicted subcellular localization using the NeMeSys database, the UniProt database, and/or the PSORTb algorithm (30)(31)(32). Among the 375 identified proteins, 49 were predicted to be localized in the outer membrane (OM), 21 (predominantly lipoproteins) in either the inner or outer membrane (I/OM), 35 in the periplasm (P), 56 in the inner membrane (IM), and 208 in the cytosol (C), whereas the location of 6 proteins could not be inferred (no) by either database annotation or computational prediction (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this method, a total of 375 distinct proteins were quantified from both the 32°C and 37°C conditions (see Table S1 in the supplemental material). All quantified proteins were classified according to their known or predicted subcellular localization using the NeMeSys database, the UniProt database, and/or the PSORTb algorithm (30)(31)(32). Among the 375 identified proteins, 49 were predicted to be localized in the outer membrane (OM), 21 (predominantly lipoproteins) in either the inner or outer membrane (I/OM), 35 in the periplasm (P), 56 in the inner membrane (IM), and 208 in the cytosol (C), whereas the location of 6 proteins could not be inferred (no) by either database annotation or computational prediction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subcellular localization of proteins was allocated according to the annotation in the NeMeSys database (30) and/or UniProt (31). For all proteins without database annotation of subcellular localization, the PSORTb algorithm was used for prediction (32).…”
mentioning
confidence: 99%
“…meningitidis strains used in this study are derivatives of the sequenced and systematically mutagenized serogroup C clinical isolate 8013 (35,36). The comP mutants have been previously described (21 Variants in which charged residues in the identified electropositive stripe were changed to Ala (ComP R78A , ComP K94A , and ComP K108A ) were constructed by site-directed mutagenesis, and the resulting proteins were purified.…”
Section: Methodsmentioning
confidence: 99%
“…Cysteine, which is a major source of sulfur and hence essential for growth of N. meningitides, was fed about a concentration of 0.04%. Cysteine is converted to glutathione (GSH), then to glutathione sulfide by oxidation, hence controls the cellular H 2 O 2 level [35,36]. Transcriptome analysis suggested that cysteine depletion impairs sulfur supply for Fe-S protein assembly and cause oxidative stress [37].…”
Section: +mentioning
confidence: 99%